Pancasila as a Paradigm for Modern Indonesia Defense - Sulistyorini Sulistyorini (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
This study aims to see the relevance of Pancasila values as a defense paradigm in Indonesia in dealing with modern threats. This research uses doctrinal methods with statue approach. The pancasila values able to unite, collaborate with all the elements in order to achieve and realize the goals of the State of Indonesia. Pancasila values still need to be held firmly and realized in the all aspects of the Indonesian people’s life. Pancasila is a defense paradigm that has been tested in the Indonesian people struggle history in facing threats from within and outside the country. Pancasila as a defense paradigm is still very relevant to be used to deal with various forms of threats both conventional threats and modern threats as we are currently facing